Identificación de los factores asociados al síndrome Burnout en personal de carrera administrativa y personal de libre nombramiento y remoción - Jhon Javier Parra-Villalba; Marleny Cardona-Acevedo (Mundo Fesc)
In recent years, Burnout syndrome has been widely researched, especially in health personnel and teachers; however, there is little literature on administrative staff. In this sense, the present research seeks to identify factors related to Burnout under typical working conditions in public universities, related to some aspects of undervaluation of human capital. In this case, the University of Sucre. In this sense, the present descriptive research with an empirical-analytical approach, a diagnosis is made using the Maslach Burnout Inventory (MBI) questionnaire, which consists of 22 items in the form of statements, whose function is to measure professional burnout. This instrument was applied to administrative staff in order to identify the possible presence of factors associated with this syndrome, taking as a reference the nature of the positions, in this case, administrative career officials and free appointment and removal from the University of Sucre, with the purpose of suggesting an intervention strategy for the preventive management of this syndrome.